PARADIGMA ILMU KONTEMPORER DAN RELEVANSINYA DENGAN MANAJEMEN PENDIDIKAN ISLAM - Reski Dayanti; Sudadi; Yamani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article explores the relevance of contemporary scientific paradigms to the management of Islamic education. The contemporary paradigm is characterized by interdisciplinary, integrative, and holistic approaches that reject purely positivistic views. In the context of Islamic education, this paradigm can be combined with al-Faruqi’s Islamization of knowledge, al-Attas’ concept of insan adabi, and Amin Abdullah’s approach to the interconnectedness of sciences. Islamic educational management is based on the principles of tawhid, trust (amanah), justice, and consultation (shura), thus functioning not only administratively but also spiritually. A critical analysis reveals that integrating the contemporary paradigm offers opportunities for curriculum innovation and the use of digital technology, while also posing challenges such as the secularization of knowledge and the commercialization of education. As a solution, transformative Islamic leadership is needed to balance modernization with Islamic values. The article concludes that integrating contemporary paradigms with Islamic educational management can produce a generation of insan kamil—intelligent, faithful, and virtuous individuals.